Revitalisasi Kawasan Candi Borobudur, Magelang, Jawa Tengah Revitalizatlon Of Borobudur Temple Area, Magelang, Central Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Bowbudur Temple has its own magnet to more than 2 million tourists both domestic and foreign tourists. This research aim is to study revitalization aspect needed in Borobudur Temple area. The main problem in Borobudur is the degradation of environment physical quality, the decline of visitor experience quality, and the decline of Borobudur image as world heritage site. Methods used in this research is qualitatim methods with rasionalistic paradigm While analyses tool used in this research consist of socio culture analyses, sosio-economy analyses, land use analyses, and tourism analyses. The findings of development analyses is a basic and strategic action to develop physical and non-physical Borobudur Temple area find its environment thus Borobudur can defend its image as a world heritage sire. This research concluded that Revitalization of Borobudur temple Area is absolutely needed. Revitalization of liorobudur Temple Area will cover development of Zone 2 and 3, so it will contribute benefit to the development of Borobudur area anal as surroundings.